ANOMALI MONDAY EFFECT PADA IHSG DI BURSA EFEK INDONESIA PERIODE 2009-2011 - Oktafalia Marisa (Universitas Bunda Mulia, 2017)
The likelihood of a market correction before the holidays due to the uneven distribution of information, which means a change or a rise and fall of stock prices in the market are always influenced by the information that is important and relevant. To avoid the uncertainty and mitigate risk, market participants behave better not hold shares of the holidays. This research wants to analyze whether there is influence of the holiday (holiday effect) to the Composite Stock Price Index (CSPI) in Indonesia Stock Exchange in the period 2009-2011. Researchers will use the closing price of the shares belonging to the JCI 1 (one) week prior to the holiday and 1 (one) week after the holiday. The results using dummy regression showed that discovered the existence of the phenomenon of Anomaly Holiday Effect on Stock Price Index (CSPI) in Indonesia Stock Exchange (IDX) during the observation period. Based on observation of the data that has been processed, it can be also a national holiday that has the most significant effect on the normal trading day of Eid. Where the conditions of the market after the holiday is very significant and fluctuated.Keyword : Anomali Monday effect, IHSG